ANALISIS DAYA SAING EKONOMI DI KABUPATEN LABUHANBATU SELATAN - Paicakra Prianti; Inggrita Gusti Sari Nasution (Departemen Ekonomi Pembangunan USU, 2015)
This study aimed to analyze the factors that affect and be decisive economic competitiveness in South Labuhanbatu District by using the method of Analytical Hierarchy Process (AHP). By using purposive sampling method, this study uses primary data with questionnaires and interviews with 30 respondents consisting of students, teachers, community public, bureaucracy, banking, non-banking, and entrepreneurs.The results from this research that the infrastructure factor becomes the most important factor in improving economic competitiveness in South Labuhanbatu District with a weight of (0,278), followed by a regional economy factor (0,275), then the labor and productivity factors (0,184), institutional factors (0,151), and the final is socio political factor (0,110).Keywords : Economic Competitiveness, Analytical Hierarchy Process